Escorting Fred Extracts from an Ashton diary - Kavanagh, Julie (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Extracts from an Ashton diary. - Preview of White Nights and lunch, 21 January 1987. - Liaisons Dangereuses and dinner, 9 July 1987. - Preview of Whales of August and dinner, 3rd November 1987. - Dinner with Selina Hastings, Chalk Farm, 9 December 1987. PALABRAS CLAVE: Frederick Ashton, diary.
Dentro del apartado "Celebrating Frederick Ashton. 17 September 1904 - 19 August 1988".